2014
DOI: 10.2147/ijn.s60938
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bioavailability of apigenin via preparation of a carbon nanopowder solid dispersion

Abstract: In this study, a novel carbon nanopowder (CNP) drug carrier was developed to improve the oral bioavailability of apigenin (AP). Solid dispersions (SDs) of AP with CNP were prepared, and their in vitro drug release and in vivo performance were evaluated. The physicochemical properties of the formulations were examined by differential scanning calorimetry, X-ray diffraction, and scanning electron microscopy. Drug release profiles showed that AP dissolution from the CNP-AP system (weight ratio, 6:1) after 60 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 28 publications
0
57
0
Order By: Relevance
“…It would still be a challenge to prove our molecular study results using in vivo animal models in our future work, since apigenin only exhibited moderate solubility in lipid (0.001-1.63 mg/mL) and water (2.16 µg/mL in water) (Ding et al, 2014). However, numerous in vivo studies revealed that apigenin showed ideal bioactivities in animal models given oral administration.…”
Section: Apigenin Induces Ros Accumulation In Pancreatic Cancer Cellsmentioning
confidence: 93%
“…It would still be a challenge to prove our molecular study results using in vivo animal models in our future work, since apigenin only exhibited moderate solubility in lipid (0.001-1.63 mg/mL) and water (2.16 µg/mL in water) (Ding et al, 2014). However, numerous in vivo studies revealed that apigenin showed ideal bioactivities in animal models given oral administration.…”
Section: Apigenin Induces Ros Accumulation In Pancreatic Cancer Cellsmentioning
confidence: 93%
“…Formulations using carbon nanopowder solid dispersions for apigenin have proven to enhance its bioavailability. These apigenin nanoparticles showed low levels of toxicity in animals [236]. Apigenin-loaded lipid nanocapsules prepared with phase inversion method showed high efficacy in restricting breast and liver cancer growth [237].…”
Section: 0 Major Limitations Of Apigeninmentioning
confidence: 99%
“…These challenges could be overcomed by new "lipid-based nano-encapsulation approaches" for targeted delivery of these functional compounds (Esfanjani, Assadpour, & Jafari, 2018). Innovative technologies such as nanocrystals, lipid-based nanoparticles including liposomes, phytosomes, micelles, solid lipid nanoparticles, microemulsions, and nanoemulsions, and solubility enhancing agents such as cyclodextrin have been reported for improvement of beneficial effects of celery's compounds (Dang et al, 2014;Ding, Zhang, et al, 2014;Huang et al, 2016;Khan, Saraf, & Saraf, 2016;Kim, Cho, & Park, 2016;Luo et al, 2019;Mahalapbutr et al, 2019;Shi, Zhao, Firempong, & Xu, 2016;Shin et al, 2018;Telange et al, 2017;Wu, Li, Yue, Zhang, & Yunusi, 2018;Wu et al, 2017;Zhai et al, 2013;Zhang, Huang, Liu, Gao, & Qian, 2013;Zhang, Cui, Wei, & Lv, 2017;Zhao, Wang, & Li, 2016). The effects of celery on metabolic syndrome are shown in Figure 2.…”
mentioning
confidence: 99%